2021
DOI: 10.3389/fendo.2021.687586
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated With Altered mRNA and miRNA Content in Human Circulating Extracellular Vesicles

Abstract: As mediators of intercellular communication, circulating extracellular vehicles (EVs) can modulate tissue and cellular pathways by altering transcription profiles in recipient cells, and their content may reflect the status of their parent cells. However, whether their cargo is altered in the metabolic syndrome (Mets) remains unclear. We hypothesized that MetS altered mRNAs and miRNAs packed within circulating-EVs. EVs were collected from plasma of patients with MetS or age-matched Lean controls (n=4 each). RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Furthermore, females with normal hematological and biochemical parameters showed no changes in sEVs and obese females showed lower expression of miR-132 and miR-26b in the sEVs enriched fraction than obese females with hyperlipidemia. These results agree with other studies that demonstrated that changes in EVs and associated miRNA were related to metabolic dysfunctions, such as hypertriglyceridemia, in obese humans 34 , 35 , 45 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, females with normal hematological and biochemical parameters showed no changes in sEVs and obese females showed lower expression of miR-132 and miR-26b in the sEVs enriched fraction than obese females with hyperlipidemia. These results agree with other studies that demonstrated that changes in EVs and associated miRNA were related to metabolic dysfunctions, such as hypertriglyceridemia, in obese humans 34 , 35 , 45 .…”
Section: Discussionsupporting
confidence: 93%
“…In vitro , detected in both human and swine MSCs with metabolic syndrome, suggesting a shared disorder process ( 75 ). Circulating exosomes in transition dairy cows were assessed in one study, and specific proteins, including α-2 macroglobulin, fibrinogen, and oncoprotein-induced transcript 3, were identified in exosomes from the serum of high-risk cows that are prone to metabolic syndrome and liver disease ( 76 ).…”
Section: Extracellular Vesicles As Biomarkersmentioning
confidence: 99%
“…[124] Moreover, cecum and liver metabolic signatures have been described in obese mice using the high-fat diet (HFD) model. [125] Interestingly, circulating microRNAs are known modulators of metabolic profiles [45,126,127] and might also influence gut microbiota, [128][129][130] which in turn may alter the systemic metabolome. Therefore, it is crucial to localize the origin of specific metabolites to precisely address the influence of each factor on liver disease onset and progression.…”
Section: Applications In Liver Diseasementioning
confidence: 99%